Ethical challenges in mass drug administration for reducing childhood mortality: a qualitative study - Ahmed Alasmar; Alex C. Kong; Anthony D. So; Matthew DeCamp (BMC, 2022)
Abstract Background Mass drug administration (MDA) of medications to entire at-risk communities or populations has shown promise in the control and elimination of global infectious diseases. MDA of the broad-spectrum antibiotic azithromycin has demonstrated the potential to reduce childhood mortality in children at risk of premature death in some global settings. However, MDA of antibiotics raises complex ethical challenges, including weighing near-term benefits against longer-term risks-particularly the development of antimicrobial resistance that could diminish antibiotic effectiveness for current or future generations. The aim of this study was to understand how key actors involved in MDA perceive the ethical challenges of MDA. Methods We conducted 35 semi-structured interviews from December 2020-February 2022 with investigators, funders, bioethicists, research ethics committee members, industry representatives, and others from both high-income countries (HICs) and low- and middle-income countries (LMICs). Interview participants were identified via one of seven MDA studies purposively chosen to represent diversity in terms of use of the antibiotic azithromycin; use of a primary mortality endpoint; and whether the study occurred in a high child mortality country. Data were analyzed using constructivist grounded theory methodology. Results The most frequently discussed ethical challenges related to meaningful community engagement, how to weigh risks and benefits, and the need to target MDA We developed a concept map of how participants considered ethical issues in MDA for child mortality; it emphasizes MDA's place alongside other public health interventions, empowerment, and equity. Concerns over an ethical double standard in weighing risks and benefits emerged as a unifying theme, albeit one that participants interpreted in radically different ways. Some thought MDA for reducing child mortality was ethically obligatory; others suggested it was impermissible. Conclusions Ethical challenges raised by MDA of antibiotics for childhood mortality-which span socio-cultural issues, the environment, and effects on future generations-require consideration beyond traditional clinical trial review. The appropriate role of MDA also requires attention to concerns over ethical double standards and power dynamics in global health that affect how we view antibiotic use in HICs versus LMICs. Our findings suggest the need to develop additional, comprehensive guidance on managing ethical challenges in MDA. Graphical Abstract